MENINGKATKAN KEMAMPUAN KOMUNIKASI LISAN ANAK USIA 4-5 TAHUN MELALUI METODE BERMAIN PERAN MAKRO DI RA IZZATUL ISLAM KARAWANG TIMUR - Nur Utami, Fitria; Supriatna, Asep; Kurniasih, Kurniasih (Penerbit Lafadz Jaya, 2026)
This study aims to improve the speaking skills of 4–5-year-old children through the application of the macro role-playing method at RA Izzatul Islam Karawang Timur. The research subjects consisted of 21 children in the Utsman Bin Affan class. The study used a Classroom Action Research (CAR) design with data collection through observation, field notes, and recordings of learning activities, which were then analyzed using descriptive qualitative methods. The results of the study indicate that the consistent application of the macro role-playing method effectively improves children's speaking skills, including listening skills, expressing opinions, expressing feelings, and interacting in conversations. These findings confirm that the macro role-playing method is effective in early childhood education for developing language skills, enhancing social interaction, building self-confidence, and stimulating children's creative thinking abilities.